Determination of Notary Fees Related to Authentic Deed Preparation Services According to Laws and Regulations in Indonesia - Indarwati, Anik (Dinasti Research, 2025)
The notary profession in Indonesia, limited to graduates of Master’s in Notarial Studies, is increasingly popular due to its stable prospects. However, the growing number of notaries in each city has intensified competition, sometimes leading to unethical practices such as underpricing deed services and discrediting peers. These behaviors conflict with the Notary Position Law and the Notary Code of Ethics. A key issue is how notary and Land Deed Official (PPAT) fees for authentic deed services are regulated. This study uses normative legal research to explore the legal basis for setting notary fees, revealing that while upper fee limits are stipulated in the Notary Position Law, sociological and economic factors also influence honorarium decisions. Disharmony between the Notary Law and the Code of Ethics creates ambiguity in setting minimum and maximum fees, potentially leading to unhealthy competition and reduced service quality. Therefore, clear and uniform fee guidelines are essential to maintain ethical standards, ensure fair compensation, and uphold the quality of authentic deed preparation.